Atlantic salmon (Salmo salar) postsmolts adapt lipid digestion according to elevated dietary wax esters from Calanus finmarchicus - Bogevik, Andre S; Tocher, Douglas R; Langmyhr, Eyolf; Waagbo, Rune; Olsen, Rolf E (Aquaculture Nutrition, 2009)
Wax esters in copepods constitute huge natural marine lipid resources, which can contribute as future lipid source in formulated diets in aquaculture, and thereby reduce the pressure on use of marine resources at higher trophic levels. The present study was undertaken to investigate factors affecting wax ester digestibility, including production of bile and lipases, in Atlantic salmon fed diets containing high proportions of an oil derived from copepods. Individually tagged postsmolt Atlantic salmon (initial weight 250 g) were distributed into three dietary groups in triplicate tanks and fed either a fish oil supplemented diet, or diets where 50% or 100% of the fish oil was replaced with oil extracted from Calanus finmarchicus. Wax esters accounted for 307 or 477 g kg-1 of the lipids in these latter diets, respectively. Over the 100 day feeding period, the salmon fed the fish oil diet displayed a significantly higher specific growth rate (SGR; 0.74) than fish fed the 100% Calanus oil diet (SGR; 0.67). The apparent digestibility coefficient of total lipid and total fatty acids was significantly higher in salmon fed the fish oil and the mixed diet than in fish fed the pure Calanus oil diet. However, the fish appeared to adjust lipid digestibility to the increased intake of wax ester by enhancing bile volume and the lipolytic activity. The study indicates that Atlantic salmon show adaptations in digestion to elevated dietary wax ester intakes, however with an upper limit for optimal utilization in practical diets.